A subset of pediatric-type thalamic gliomas share a distinct DNA methylation profile, H3K27me3 loss and frequent alteration of EGFR. Issue 1 (1st November 2020) - Sievers, Philipp; Sill, Martin; Schrimpf, Daniel; Stichel, Damian; Reuss, David E; Sturm, Dominik; Hench, Jürgen; Frank, Stephan; Krskova, Lenka; Vicha, Ales; Zapotocky, Michal; Bison, Brigitte; et al.
Abstract: Background: Malignant astrocytic gliomas in children show a remarkable biological and clinical diversity. Small in-frame insertions or missense mutations in the epidermal growth factor receptor gene ( EGFR ) have recently been identified in a distinct subset of pediatric-type bithalamic gliomas with a unique DNA methylation pattern. Methods: Here, we investigated an epigenetically homogeneous cohort of malignant gliomas ( n = 58) distinct from other subtypes and enriched for pediatric cases and thalamic location, in comparison with this recently identified subtype of pediatric bithalamic gliomas. Results: EGFR gene amplification was detected in 16/58 (27%) tumors, and missense mutations or small in-frame insertions in EGFR were found in 20/30 tumors with available sequencing data (67%; 5 of them co-occurring with EGFR amplification). Additionally, 8 of the 30 tumors (27%) harbored an H3.1 or H3.3 K27M mutation (6 of them with a concomitant EGFR alteration). All tumors tested showed loss of H3K27me3 staining, with evidence of overexpression of the EZH inhibitory protein (EZHIP) in the H3 wildtype cases. Although some tumors indeed showed a bithalamic growth pattern, a significant proportion of tumors occurred in the unilateral thalamus or in other (predominantly midline) locations. Conclusions: Our findings present a distinct molecular class of pediatric-type malignant gliomas largely overlapping with the recently reported bithalamic gliomas characterized by EGFR alteration, but additionally showing a broader spectrum of EGFR alterations and tumor localization. Global H3K27me3 loss in this group appears to be mediated by either H3 K27 mutation or EZHIP overexpression. EGFR inhibition may represent a potential therapeutic strategy in these highly aggressive gliomas.